2018
DOI: 10.1124/jpet.117.247130
|View full text |Cite
|
Sign up to set email alerts
|

CYP4X1 Inhibition by Flavonoid CH625 Normalizes Glioma Vasculature through Reprogramming TAMs via CB2 and EGFR-STAT3 Axis

Abstract: Tumor-associated macrophages (TAMs) are pivotal effector cells in angiogenesis. Here, we tested whether CYP4X1 inhibition in TAMs by flavonoid CH625 prolongs survival and normalizes glioma vasculature. CH625 was selected against the CYP4X1 3D model by virtual screening and showed inhibitory activity on the CYP4X1 catalytic production of 14,15-EET-EA in the M2-polarized human peripheral blood mononuclear cells (IC = 16.5 M). CH625 improved survival and reduced tumor burden in the C6 and GL261 glioma intracrania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…CYP4X1, monooxygenases, encodes a member of the cytochrome P450 superfamily of enzymes. Wang et al suggested that CYP4X1 inhibition can prolong the survival rate of glioma (45). In accordance with these, our study has shown that iron metabolism-related genes are correlated with the prognosis of ccRCC, but their actual effects and potential mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 89%
“…CYP4X1, monooxygenases, encodes a member of the cytochrome P450 superfamily of enzymes. Wang et al suggested that CYP4X1 inhibition can prolong the survival rate of glioma (45). In accordance with these, our study has shown that iron metabolism-related genes are correlated with the prognosis of ccRCC, but their actual effects and potential mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 89%
“…The tumor perfusion was measured by laser Doppler analysis as previously described [16, 25]. Briefly, the C6-bearing rats as described above were anesthetized with 0.6% pentobarbital and placed on a heating pad (37 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Restoring the expression of MGLL in tumor tissues and targeting CB2 are new strategies for tumor immunotherapy. However, the flavonoid CH625 inhibits CYP4X1 through the CB2 and EGFR-STAT3 axis to reprogram TAMs away from M2 type, and normalizes the blood vessels of gliomas (151). This also indicates that CB2 can inhibit tumor progression, which may be different from tumor types and the specific mechanism deserves further exploration.…”
Section: Tlr Receptorsmentioning
confidence: 99%